Safety and Effectiveness of Bivalirudin in Patients Undergoing Percutaneous Coronary Intervention: A Systematic Review and Meta-Analysis - Ahmad Hamdi, Abdul Hafeez; Dali, Ahmad Fauzi; Mat Nuri, Thimarul Huda; Saleh, Muhammad Syafiq; Ajmi, Noor Nabila; Neoh, Chin Fen; Ming, Long Chiau; Abdullah, Amir Heberd; Khan, Tahir Mehmood (Frontiers in Pharmacology, 2017)
Recent clinical trials have shown that while bivalirudin exhibits similar efficacy with heparin, it offers several advantages over heparin such as a better safety profile. We aimed to evaluate the efficacy and safety of bivalirudin use during Percutaneous Coronary Intervention (PCI) in the treatment of angina and acute coronary syndrome (ACS). We searched the Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, PubMed, EMBASE, and Science Direct from January 1980 to January 2016. Randomized controlled trials (RCTs) comparing bivalirudin to heparin during the course of PCI in patients with angina or ACS were included. Outcome measures included all-cause mortality, myocardial infarction, revascularisation, stent thrombosis, stroke, and major bleeding. The selection, quality assessment, and data extraction of the included trials were done independently by four authors, and disagreements were resolved by consensus. Pooled relative risk (RR) estimates and 95% confidence intervals (CIs) were calculated. A total of twelve RCTs involving 44,088 subjects were included. Bivalirudin appeared to be non-superior compared to heparin in reducing all-cause mortality, myocardial infarction, revascularisation, and stroke. Bivalirudin appeared to be related to a higher risk of stent thrombosis when compared to heparin plus provisional use of a glycoprotein IIb/IIIa inhibitor (GPI) at day 30 (RR 1.94 [1.16, 3.24] p< 0.01). Overall, bivalirudin-based regimens present a lesser risk of major bleeding (RR 0.56 [0.44–0.71] p< 0.001), and Thrombolysis In Myocardial Infarction (TIMI) major bleeding (RR 0.56 [0.43–0.73]) compared with heparin-based regimens either with provisional or routine use of a GPI. However, the magnitude of TIMI major bleeding effect varied greatly (p< 0.001), depending on whether a GPI was provisionally used (RR 0.42 [0.34–0.52] p< 0.001) or routinely used (RR 0.60 [0.43 –0.83] p< 0.001), in the heparin arm. This meta-analysis demonstrated that bivalirudin is associated with a lower risk of major bleeding, but a higher risk of stent thrombosis compared to heparin.